Advances and trends in industrial combustion to improve efficiency in hot rolling processes: A Systematic Review - Quispe Laguna, Angel Rapahel; Flores Idrugo, Eddier Albino (LACCEI, 2025)
This study performs a systematic review of the literature on oxygen enrichment, oxygen lances and oxy-fuel technologies based on the use of pure oxygen in the combustion process in reheating furnaces for hot rolling mills, focusing on the improvement of combustion efficiency and productivity. The information search was carried out in the Scopus database, where 18 articles were identified and selected using the PRISMA and PICO methods. Subsequently, a bibliometric analysis was performed to obtain a deeper insight into the research conducted on oxygen enrichment and oxy-combustion as technologies in heating processes. Tools such as VOSviewer to visualize the cooperation between researchers from different countries in related scientific production and Bibliometrix to graphically represent the countries with the highest scientific production were used.